eCM 2013
DOI: 10.22203/ecm.v025a19
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of parathyroid hormone-mediated suppression of calcification markers in human intervertebral disc cells

Abstract: In degenerative intervertebral discs (IVD), type X collagen (COL X) expression (associated with hypertrophic differentiation) and calcification has been demonstrated. Suppression of COL X expression and calcification during disc degeneration can be therapeutic. In the present study we investigated the potential of human parathyroid hormone 1-34 (PTH) in suppressing indicators of calcification potential (alkaline phosphatase (ALP), Ca 2+ , inorganic phosphate (Pi)), and COL X expression. Further, we sought to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…However, these changes were effectively attenuated by PTH(1-34) treatment. Consistent with a previous study, Madiraju and colleagues (28) reported that PTH can stimulate type II collagen and proteoglycan synthesis by acting via MAPK and PKA signaling pathways to retard intervertebral disc (IVD) degeneration. Thus, PTH(1-34) treatment retards ASDD partly by regulating molecular metabolism.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 82%
See 1 more Smart Citation
“…However, these changes were effectively attenuated by PTH(1-34) treatment. Consistent with a previous study, Madiraju and colleagues (28) reported that PTH can stimulate type II collagen and proteoglycan synthesis by acting via MAPK and PKA signaling pathways to retard intervertebral disc (IVD) degeneration. Thus, PTH(1-34) treatment retards ASDD partly by regulating molecular metabolism.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 82%
“…Parathyroid hormone (PTH) has been shown to increase vertebral bone mass in patients with postmenopausal osteoporosis, (15) promote fracture healing, (16) and improve spinal fusion. (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) Moreover, Madiraju and colleagues (28) reported that PTH stimulates matrix synthesis and suppresses markers of calcification potential in degenerated disc cells via MAPK and PKA signaling pathways. Furthermore, Ishikawa and colleagues (29) reported that PTH stimulated the synthesis of cellular and extracellular proteins by growth plate chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix of the intervertebral disc is mainly composed of Aggrecan, collagen and elastin, and oestrogen and parathyroid hormone (PTH) have an important role in promoting their metabolism1516. In addition, oestrogen receptors α and β were found in both the NP and the AF, and experiments confirmed that oestrogen can directly improve the proliferative activity of cells in the NP and annulus fibrosus and reverse their apoptosis171819.…”
mentioning
confidence: 99%
“…After pressure loading with 0.2 MPa or 0.8 MPa for three days, expressions of NP related gene SOX9, COL II , and ACAN were all upregulated. COL I and COL X were reported to highly express when NP tissue underwent degeneration . After preconditioning, both of the two genes were downregulated in our system.…”
Section: Discussionmentioning
confidence: 65%
“…COL I and COL X were reported to highly express when NP tissue underwent degeneration. 49 After preconditioning, both of the two genes were downregulated in our system. Subsequent injection and histological staining proved the successful implantation of MSCs-laden PMs in vivo, where chondrogenic commitment to NP-like cells was maintained.…”
Section: Discussionmentioning
confidence: 81%